Securing Futures: The Inuvialuit Regional Corporation and Reindeer Herding History - Salo, Mervi Maarit (Journal of Aboriginal Economic Development, 2025)
This article explores the complex history of reindeer herding in North America and contextualizes its connection to other Arctic Indigenous nations, from the Sámi people to its contemporary management by the Inuvialuit Regional Corporation (IRC). Reindeer herding was initially introduced in North America in the late nineteenth century as a solution to declining caribou populations and this practice evolved over time into its modern context with the IRC. By acquiring Canada’s only reindeer herd in 2021 and spearheading initiatives like the Country Food Processing Plant in Inuvik, the IRC is integrating traditional herding practices within a corporate framework to ensure sustainable development, food security, and local job creation, while also highlighting the importance of economic development in Indigenous self-determination. This article provides insight into how the IRC’s management of the reindeer herd represents an innovative model of Indigenous economic empowerment, blending culture with strategic economic initiatives to address contemporary challenges. The article contributes to the broader discourse on Indigenous governance, economic sustainability, and the pivotal role of traditional knowledge in shaping future pathways for Indigenous communities in the Arctic and beyond.